(untitled) (Hoboken, N.J., 2007)
Based on the results of a more than two-year study, Lead-Free Electronics: iNEMI Projects Lead to Successful Manufacturing is the first practical, primary reference to cover Pb-free solder assembly as well as the analysis and reasoning behind the selection of Sn-Ag-Cu as the recommended Pb-free replacement for Sn-Pb.
Keywords: Solder and soldering,Lead-free electronics manufacturing processes,Hàn và mối hàn,Quy trình sản xuất thiết bị điện tử chì